Distributional impacts of cash allowances for children: A microsimulation analysis for Russia and Europe - Daria Popova (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper analyses programmes of cash allowances for children and compares their effectiveness in combating child poverty in Russia and four EU countries Sweden, Germany, Belgium and the United Kingdom. These countries are selected as representatives of alternative family policy models. Using microsimulation models (RUSMOD and EUROMOD), this paper estimates the potential gains if the Russian system were re-designed along the policy parameters of these countries and vice versa. Such an exercise rests on the idea of policy learning and provides policy relevant evidence on how a policy would perform, given different national socio-economic and demographic settings. The results confirm that the poverty impact of the program design is smaller than that of the level of spending. Other conditions being equal, the best outcomes for children are achieved by applying the mix of universal and means-tested child benefits, such as those employed by the UK and Belgium. At the same time, the Russian design of child allowances does not appear to be less effective in terms of its impact on child poverty when transferred to European countries in place of their current arrangements.
Keywords: C81; D31; I38; 330; family policy; child benefits; microsimulation; Russia